Implementation of the Cooperative Integrated Reading and Composition Learning Model to Increase The Interest in Reading of Physical Education Students - Ari Sutisyana; Yahya Eko Nopiyanto; Arwin Arwin (UNIB Press, 2023)
This research is a classroom action research that aims to analyze the increase in physical education students' interest in reading in attending lectures on basic research and scientific writing. The research method used is classroom action research using 2 cycles. The participants in this study were physical education students who attended basic research lectures and scientific writing totaling 52 students. Data collection techniques and instruments used observation guides, questionnaires, and interviews. Research data were analyzed using a combination of quantitative and qualitative. The results of the analysis show that in cycle 1 the reading interest of physical education students is in the medium category, and the reading interest of physical education students in cycle 2 is in the high category. So, it can be concluded that the CIRC learning model is effective in increasing students' interest in reading. It can be used as a recommendation for Physical Education lecturers to make this learning model an alternative to managing the learning process.